Access to healthy ınformatıon: the ınteractıon of medıa lıteracy and health lıteracy - Hatice Mutlu; Gözde Bozkurt; Gökten Öngel; Yağmur Gümüşboğa (BMC Public Health)
Abstract Objective Grounded in the Health Belief Model (HBM) and Media System Dependency Theory (MSDT), this study examines the relationship between media literacy and health literacy in the Turkish context, where digital media plays an increasingly dominant role in disseminating health-related information. It focuses on how individuals access, evaluate, and utilize health information, analyzing the effects of media literacy sub-dimensions—access, analysis, evaluation, and communication—on health literacy levels. The study aims to determine how media-based health information influences individuals’ decision-making processes and their ability to make informed health choices. Methods A survey-based quantitative research approach was employed with 485 participants from Turkey, of which 477 valid responses were analyzed. The Turkish Health Literacy Scale (TSOY-32) measured health literacy, while the Media Literacy Skills Scale assessed media literacy. The Generalized Ordered Logit Model (GOLM) was applied to examine the effects of media literacy on health literacy. Results Descriptive statistics, correlation analysis, and hypothesis testing were conducted. Media literacy levels significantly influence health literacy levels (p < 0.05). The access sub-dimension increased the likelihood of improving health literacy by 1.90 times (p < 0.05). The analysis sub-dimension significantly enhanced health literacy by 2.23 times (p < 0.05). The evaluation sub-dimension had a statistically significant effect on health literacy (p < 0.05). The communication sub-dimension supports individuals in sharing health information and making informed decisions (p < 0.05). Health recommendations disseminated through media significantly impact health literacy levels (p < 0.05). Trust in media-based health information had a weak but positive correlation with health literacy (r = 0.2097, p < 0.05). Education level was positively correlated with health literacy, while income level showed no significant effect. These findings suggest that enhancing media literacy skills, particularly in access and analysis, can meaningfully improve individuals’ capacity to navigate complex health information landscapes and foster more informed health behaviors. Conclusion The study highlights the crucial role of media literacy in improving health literacy and preventing misinformation. Access and analysis skills are particularly vital in enabling individuals to obtain accurate health information and avoid misleading content. Conducted within the Turkish sociocultural context, where digital media usage is high and misinformation about health is prevalent, the findings offer valuable insights for national health promotion strategies. Policymakers and educators should integrate media literacy into educational curricula, launch public awareness campaigns to combat misinformation, and develop strategies to enhance individuals’ critical thinking skills regarding health information. This study is limited by its cross-sectional design and reliance on self-reported data. Future research should employ longitudinal methods and explore the long-term impact of media and health literacy across different demographic groups and contexts.